Optimal treatment of ceftazidime-avibactam and aztreonam-avibactam against bloodstream infections or lower respiratory tract infections caused by extensively drug-resistant or pan drug-resistant (XDR/PDR) Pseudomonas aeruginosa - Kang, Yixin; Xie, Lu; Yang, Jiyong; Cui, Junchang (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To evaluate the efficacy of ceftazidime-avibactam (CZA) and aztreonam-avibactam (AZA) against bloodstream infections (BSIs) or lower respiratory tract infections (LRTIs) – caused by extensive drug-resistant or pan drug-resistant (XDR/PDR) Pseudomonas aeruginosa. Method The two-fold dilution method was used to determine the minimum inhibitory concentrations (MICs) of CZA/AZA against XDR/PDR P. aeruginosa. Whole-genome sequencing was used to analyze the resistance determinants of each isolate. Monte Carlo simulations (MCSs) were used to evaluate the probability of target attainment (PTA) and the cumulative fraction of response (CFR) of each CZA/AZA dosing regimen via traditional infusion (TI)/optimized two-step-administration therapy (OTAT). Results We found that XDR/PDR P. aeruginosa may carry some rare MBLs (e.g.: IND-6, SLB-1, THIN-B). P. aeruginosa isolates producing IMP-45, VIM-1, or VIM-2 were inhibited by AZA at a concentration of 2 to 8 mg/L. All isolates producing IND-6 plus other serine β-lactamases were high-level resistant to CZA/AZA (MICs >64 mg/L). All simulated dosing regimens of CZA/AZA against BSIs-causing XDR/PDR P. aeruginosa achieved 100% PTA when the MIC was ≤32 mg/L. Conclusion AZA has been considered as an option for the treatment of infections caused by XDR/PDR P. aeruginosa producing IMP-45, VIM-1, or VIM-2. OTAT with sufficient pharmacodynamic exposure may be an optimal treatment option for XDR/PDR P. aeruginosa with a high-level MIC of CZA/AZA.